Assessment and GIS mapping of DTPA-extractable cationic micronutrients and hot water-soluble boron in soils of Rajouri District, Jammu & Kashmir, India - Renuka; Sarabdeep, Kour; Vikas, Sharma; Meenakshi, Gupta; Divya, Sharma; Rajeev, Bharat; Dhamni, Patyal (Plant Science Today, 2026)
Increased production of crops utilising high yielding varieties requires larger input of macronutrients which has accelerated micronutrient deficiencies in soils. The soil micronutrient status indicates extent of depletion and future projections for prediction of their requirements, refinement of critical levels and delineation of micronutrient deficient and toxic areas. This study was carried out with the objective of generating soil fertility maps of Rajouri District of Jammu & Kashmir using geographical information system (GIS) approach. Mapping of diethylene triamine pentaacetic acid (DTPA)-extractable cationic micronutrients and hot water-soluble boron (B) was carried out. Soil samples were collected from various land uses viz: agriculture, horticulture, forest, pasture and waste lands. The spatial visualisation of maps was done using inverse distance weight (IDW). The soil was found to be moderately acidic to moderately alkaline in reaction (pH 4.9 to 9.0) and free from the problem of salinity. The soil organic carbon (OC) content in the district ranged between 1.20 and 25.80 g kg-1. The DTPA-iron (Fe), manganese (Mn), zinc (Zn) and copper (Cu) content in soils varied from 1.26 to 58.03 mg kg-1, traces to 58.15 mg kg-1, 0.20 to 4.82 mg kg-1 and traces to 10.69 mg kg-1 respectively under various land use systems whereas hot water soluble B content varied from 0.10 to 5.95 mg kg-1. The content of Fe, Mn and Zn were higher in agricultural soils, whereas Cu and B content were found higher under horticultural soils. Soil micronutrient maps clearly showed areas where lack of micronutrients limited crop growth. Zinc was deficient in >50 % of sites; Fe and Mn were sufficient in >95 % of sites, 5 % sites were having low B content and approximately 35 % sites were having low copper content. The values of micronutrient content, organic carbon and clay content had a positive relationship. The study emphasises the need for targeted nutrient management strategies; especially zinc fertilisation in deficient areas, to support crop productivity. Additionally, managing organic matter and carefully using micronutrient fertilisers can help maintain long-term soil health and avoid future deficiencies.